1998
DOI: 10.3758/bf03199165
|View full text |Cite
|
Sign up to set email alerts
|

A step function in pigeons’ temporal generalization in the peak shift task

Abstract: Pigeons were reinforced for pecking a key following one signal duration (S+) but not following another signal duration (S-). The S+ and S-were 2.52 and 5.67 sec, respectively, counterbalanced across birds. Subsequent generalization tests with a range of signal durations revealed a step function, with high response rates for all durations on the S+ side of the distribution, low response rates for all durations on the S-side, and an intermediate rate for the intermediate duration. A comparison group of pigeons t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Spetch and Cheng (1998), with pigeons, found that the generalization gradients that the birds produced resembled step functions best. The birds responded at low rates in the presence of the S and all stimuli that were more similar to the S than to the S and responded at high rates in the presence of the S and all stimuli that were more similar to the S than to the S .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Spetch and Cheng (1998), with pigeons, found that the generalization gradients that the birds produced resembled step functions best. The birds responded at low rates in the presence of the S and all stimuli that were more similar to the S than to the S and responded at high rates in the presence of the S and all stimuli that were more similar to the S than to the S .…”
Section: Discussionmentioning
confidence: 98%
“…Our generalization tests did not provide any feedback to participants, whereas Spetch and Cheng (1998) interspersed reinforced S trials among the test trials, although in one experiment generalization testing was conducted in extinction. Perhaps the continued presence of reinforcement and the extended training and testing encouraged the pigeons to treat the durations as belonging to one of two categories, either "S "-like or "S "-like.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet other gradients are step functions, low on the S-side, high on the S+ side (e.g. Spetch and Cheng 1998).…”
Section: Peak Shiftmentioning
confidence: 99%